2017
DOI: 10.1186/s12871-017-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

Is propofol injection pain really important to patients?

Abstract: BackgroundPropofol injection pain (PIP) has been adequately studied during the past decades. However, patients’ opinion on this problem and the incidence of patients’ recall of this brief discomfort are still unknown. Thus, we conducted this study to know the patients’ perspectives on PIP and provide useful information about the incidence of recall of PIP under our routine general anesthesia.MethodsFive hundred preoperative questionnaires were distributed to patients who were scheduled for elective open thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…This may have been an effect of electromyographic activity on the calculation of BIS [ 15 ]. This study showed that the incidence and severity of pain and the frequency of recall after propofol injection were similar to those reported in previous studies [ 16 , 17 ]. Pain after propofol injection was mild, and the frequency of recall was low.…”
Section: Discussionsupporting
confidence: 90%
“…This may have been an effect of electromyographic activity on the calculation of BIS [ 15 ]. This study showed that the incidence and severity of pain and the frequency of recall after propofol injection were similar to those reported in previous studies [ 16 , 17 ]. Pain after propofol injection was mild, and the frequency of recall was low.…”
Section: Discussionsupporting
confidence: 90%
“…Though propofol injection pain is not known to be a lifethreatening complication of anesthesia, it is defined as an unpleasant situation for patients related to anesthesia [3]. According to research, the incidence risk of propofol injection pain varies from 28-90% for adults [2].…”
Section: Discussionmentioning
confidence: 99%
“…According to research, the incidence risk of propofol injection pain varies from 28-90% for adults [2]. Propofol injection pain is a research area that has attracted the interest of many researchers and when the literature is examined, in 2011, 177 clinical studies including over 25,000 cases appear to be related to propofol injection pain [3]. Methods and medications applied to prevent propofol injection pain have been investigated from aspects such as causing increasing labor in the intense operating room process and financial resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations